Network routing .Fundamentals,applications, and emerging technologies - Misra Sudip; Sumit Goswami (Wiley, 2017)
Network Routing: Fundamentals, Applications and Emerging Technologies serves as single point of reference for both advanced undergraduate and graduate students studying network routing, covering both the fundamental and more moderately advanced concepts of routing in traditional data networks such as the Internet, and emerging routing concepts currently being researched and developed, such as cellular networks, wireless ad hoc networks, sensor networks, and low power networks.
Keywords: Routing (Computer network management)